Global Regulatory Frameworks for Fermented Foods: A Review - Mukherjee, Arghya; Gómez-Sala, Beatriz; O'Connor, Eibhlís M.; Kenny, John G.; Cotter, Paul D. (Frontiers in Nutrition, 2022)
In recent years, there has been a global resurgence of public interest in fermented foods. In parallel, there have been several new studies that associate the consumption of fermented foods with a variety of beneficial impacts. These combined developments have led to a renewed focus in research and innovation vis-à-vis fermented foods, particularly traditional fermented foods, with an aim to harness this information to develop novel fermented foodstuffs and ingredients and make them available in the market. Consequently, an ever greater and more diverse array of fermented foods, including functional fermented foods with health benefits, are becoming available for public consumption in global markets, with the number expected to grow substantially in the coming decade. This rapidly expanding portfolio of commercially available fermented foods has in turn required an evolution in the corresponding global regulatory frameworks. Due to the innovative and emerging nature of these foods, combined with historical differences in regulator approaches, significant disharmony exists across these frameworks, with individual nations and organizations often adopting unique approaches relating to the establishment of standards and specifications. In this review, we provide an overview of the current regulatory frameworks for a diversity of fermented foods across multiple jurisdictions, with special emphasis on differences in legislative structures and approaches, regulatory harmonization, and current legislative limitations. Overall, the review provides important perspective and context in relation to current global fermented food regulatory practices with possible directions and recommendations for future legislative efforts.